The Role of Unions in Inflation: A Survey Article - Williams, C. (Relations industrielles / Industrial Relations, 1982)
Wide divergence of views exists on the power of unions to influence the general wage level. This paper contrasts selected views. A modified Trevithick/Mulvey classification of union reaction to escess demand for labour is used to classify writers. A second part examines questions of union power and militancy.